Tantangan Etika dan Hukum Penggunaan Rekam Medis Elektronik dalam Era Personalized Medicine - Rani Tiyas Budiyanti; Penggalih Mahardika Herlambang; Nurhasmadiar Nandini (Sekolah Vokasi Universitas Gadjah Mada, 2019)
Background: Personalized medicine is one of the health treatment approaches that has developed in the last ten years. This treatment is specific because it considers the genomics of patients and requires a complete database or medical record covering clinical and genomic data. Nevertheless, there are ethical and legal challenges in the implementation of electronic medical records in personalized medicine.Objective: This study aimed to determine the ethical and legal challenges in the use of electronic medical records in personalized medicine based on previous literature.Methods: The method used in this study was literature review with sources from journals, books, and articles on electronic medical records, personalized medicine, as well as legal and ethical aspects related both domestically and abroad. Results: Ethical and legal challenges that can occurred in the use of electronic medical records in the personalized medicine era include security and ownership of data, legal responsibility, genomic discrimination, and changes in the relationship between doctors and patients.Conclusion: Indonesia does not yet have specific regulations regarding data security, data ownership, and data sharing in the health sector. Further regulations regarding the use of electronic medical records in the personalized era are needed so that their implementation does not conflict with the ethics and laws that apply in Indonesia